Addressing Vocational High School Unemployment Through Talent Mapping and Policy Reform: Mengatasi Pengangguran di Sekolah Menengah Kejuruan Melalui Pemetaan Bakat dan Reformasi Kebijakan - Alip Purnomo; Darto; Budiyanto; Nunuk Hariyati (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Vocational education in Indonesia, especially through Vocational High Schools (SMK), aims to prepare students for the workforce but paradoxically has the highest unemployment rate among educational levels (9.01% in 2024). Knowledge Gap: Limited research examines the systemic issues at micro, meso, and macro levels that hinder SMK effectiveness. Aims: This study critically evaluates these issues, including curriculum relevance, infrastructure, and policy alignment. Results: Key problems include inadequate facilities, outdated curricula, limited industry collaboration, decentralization challenges, and a utilitarian policy focus prioritizing market needs over holistic student development. Novelty: The study proposes integrating talent mapping into SMK programs to align students' potential with educational pathways, enhancing relevance and adaptability. Implications: Prioritizing individual development over short-term market demands can reduce unemployment and produce graduates with broader competencies for a dynamic workforce. Highlights: High Unemployment Rate: SMK graduates face the highest unemployment in Indonesia, reflecting systemic inefficiencies. Policy Misalignment: A utilitarian focus prioritizes market demands over holistic student development, leading to mismatches. Proposed Solution: Talent mapping and competency-based approaches can align student potential with workforce needs. Keywords: Vocational Education, Vocational High School, Training Challenge, SMK Unemployment